Combination of gemcitabine and Ad5/3-Δ24, a tropism modified conditionally replicating adenovirus, for the treatment of ovarian cancer - Raki, M; Kanerva, A; Ristimaki, A; Desmond, R A; Chen, D-T; Ranki, T; Sarkioja, M; Kangasniemi, L; Hemminki, A (Gene therapy, 2005)
Conditionally replicating adenoviruses (CRAds) represent a novel approach for the treatment of cancers resistant to conventional therapies. The efficacy of CRAds might be further improved by using chemotherapeutic agents in a multimodal antitumor approach. We have evaluated the use of Ad5/3-Δ24, a serotype 3 receptor targeted Rb/p16 pathway selective CRAd, in combination with gemcitabine against human ovarian adenocarcinoma. The combination of these agents showed synergistic cell killing in vitro compared to single treatments. However, the effect was dependent on dose and sequencing of the agents. Our results also indicate that gemcitabine reduces the initial rate of Ad5/3-Δ24 replication without affecting the total amount of virus produced. Possible reasons for synergy between Ad5/3-Δ24 and gemcitabine include the chemosensitizing activity of E1A and/or altered replication kinetics. In an orthotopic murine model of peritoneally disseminated ovarian cancer, the combination increased the survival of mice over either agent alone, and almost 60% of treated mice were cured. Sequencing of the agents was critical for toxicity versus efficacy. Mice remained free from intraperitoneal disease, but some succumbed to treatment-related hepatic or bone marrow toxicity. This suggests that improved efficacy may uncover treatment-related toxicity, which needs to be monitored closely in clinical trials.